An analysis of total quality management and customer satisfaction among mobile service users / Intan Nurjannah Mohamed Sabri and Arifha Mohamad - Mohamed Sabri, Intan Nurjannah; Mohamad, Arifha (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Customer satisfaction is one of the major concerns today. Total quality management (TQM) assists the telecommunication industry in retaining and acquiring the satisfaction of the customer. Therefore, the intention of the study is to identify the relationship between customer satisfaction and TQM in Malaysia's telecommunication industry. In addition, this study uses quantitative methods by distributing questionnaires to respondents. The distribution of questionnaires to the customer of various types of telecommunication service providers as respondent for this study. Based on Krejcie & Morgan sample size table, 384 respondents should be involved in this study. However, only 237 successful questionnaires were returned. The Statistical Packages for Social Science (SPSS) software is being utilized in this study to analyze the data obtained. The analysis consists of descriptive analysis and correlation analysis. The result shows that there is a significant relationship between TQM and customer satisfaction. This study is important to expand the understanding of the researchers toward the TQM in telecommunication sector which the focus of this study is mobile service provider such as Celcom, Digi, and Maxis.